2018
DOI: 10.2217/fon-2017-0543
|View full text |Cite
|
Sign up to set email alerts
|

Statins Use and Cancer: An Update

Abstract: After initial concerns regarding the association of statins with increased incidences of cancer and elevated cancer-related mortality, there are now plenty of data on the antitumor, cytostatic and cytotoxic effectiveness of this class of drugs. Here, we present a short review of possible mechanisms of antineoplastic activity obtained from preclinical research and the influence of statins on cancer treatment. In the second part of the article, we focus on the most recent data from observational clinical trials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 94 publications
1
39
0
Order By: Relevance
“…Importantly, lovastatin inhibits cell proliferation and migration in both ER positive and triple negative breast cancer cells, possibly due to a decrease in intracellular cholesterol levels [39], and cholesterol is able to rescue these effects of lovastatin. The anticancer effects of statins have been shown to involve multiple molecular pathways, including inhibition of protein kinase B (AKT)/mammalian target of rapamycin (mTOR) [40,41]. the Neverthless, the current study demonstrates thatin the presence of lovastatin, addition of cholesterol is able to restore the inhibitory effects of lovastatin on cell proliferation and migration of MDA-MB-231 cells via the ERRα pathway, while ERRα protein levels remain unchanged.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Importantly, lovastatin inhibits cell proliferation and migration in both ER positive and triple negative breast cancer cells, possibly due to a decrease in intracellular cholesterol levels [39], and cholesterol is able to rescue these effects of lovastatin. The anticancer effects of statins have been shown to involve multiple molecular pathways, including inhibition of protein kinase B (AKT)/mammalian target of rapamycin (mTOR) [40,41]. the Neverthless, the current study demonstrates thatin the presence of lovastatin, addition of cholesterol is able to restore the inhibitory effects of lovastatin on cell proliferation and migration of MDA-MB-231 cells via the ERRα pathway, while ERRα protein levels remain unchanged.…”
Section: Discussionmentioning
confidence: 64%
“…Also, they have shown that F232 and L228 of ERRα possibly make important hydrophobic contacts with cholesterol [29]. A limitation of our study is that cholesterol lowering drugs like statins have been reported to have cholesterol-independent effects [40,41]. Unfortunately, there are no known cholesterol depleting agents that do not exhibit cholesterol-independent effects.…”
Section: Discussionmentioning
confidence: 87%
“…Currently, statins are in use for preventing or treating cancer patients with prostate (206), breast (207), lung (208), liver (209), and other cancers (210,211). The safety, efficacy and mortality benefits of statins have been assessed both alone and in combination therapy in clinical cancer patients studies (212)(213)(214).…”
Section: Targeting Hmgcr In Clinical Cancer Therapymentioning
confidence: 99%
“…Statins may exert their anticancer effect through several molecular mechanisms: via lowering protein prenylation, reducing tumor cell proliferation and migration, inhibiting rat sarcoma (Ras) signaling, inducing apoptosis through inhibition of Akt phosphorylation and consequently mammalian target of rapamycin (mTOR) down-regulation and other pleiotropic effects on cellular level ( 57 , 58 ).…”
Section: General Conceptmentioning
confidence: 99%